Hospitality and welfare in the Late medieval Aosta Valley (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Between the 12th and the 15th centuries, the exercise of charity and hospitality in the Aosta Valley was profoundly influenced by the region's strategic location at the heart of the Western Alps. Many hospitals were built along the main routes through the valley, with the aim of offering lectum, panem et ignem to travellers and local pauperes. From the 13th century onwards, a renewed religious sensitivity favoured the foundation of new hospitals, which were later supported by numerous donations. During the 15th century, some of these institutions flourished, while others fell into ruin, depending on their location and the subsequent interest shown by the local authorities in them. The essay, based on the local bibliography and the analysis of the records of pastoral visitation of the 15th century, aims to study the various processes that affected the exercise of hospitality in the diocese of Aosta at the end of the Middle Ages.
Keywords: Hospitals; Aosta Valley; routes; Saint Bernard passes